2006
DOI: 10.1002/gps.1644
|View full text |Cite
|
Sign up to set email alerts
|

Do symptoms of memory impairment correspond to cognitive impairment: a cross sectional study of a clinical cohort

Abstract: The MCI represent a group with multiple risk factors for progression to AD. The SNCI group may represent a heterogeneous group with some individuals in the early stages of AD whilst others' memory complaints are more likely linked to anxiety or personality traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…SMC might not only to inform the current well‐being of an individual, but also potentially predict future cognitive trajectory . To date, some groups have found low correlation with objective tests while others have found a significant relationship . To some extent, this could be due to methodological issues, for example, with cross‐sectional designs.…”
Section: Introductionmentioning
confidence: 99%
“…SMC might not only to inform the current well‐being of an individual, but also potentially predict future cognitive trajectory . To date, some groups have found low correlation with objective tests while others have found a significant relationship . To some extent, this could be due to methodological issues, for example, with cross‐sectional designs.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have attempted to address whether SMC are predictive of future development of dementia rather than associated with current dementia (Jonker et al, 2000). There is uncertainty regarding the relationship between subjective and objective cognitive complaints (Bolla et al, 1991;Taylor et al, 1992;Riedel-Heller et al, 1999Archer et al, 2006;Jama et al, 2006;Reid and MacLullich, 2006). Yet it may be possible to use SMC as a form of initial screening for individuals suffering MCI or dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have compared the neurocognitive test performances of individuals with SCC relative to controls have most often found numerically lower, although intact, scores (e.g., Nutter-Upham et al, 2008; Peter et al, 2014; Reisberg, Shulman, Torossian, Leng, & Zhu, 2010). Although less frequent, a few studies have found statistically significant differences in cognition between SCC and control groups (e.g., Amariglio et al, 2012; Archer et al, 2006; Buelow, Tremont, Frakey, Grace, & Ott, 2014; Caselli et al, 2014; Dik et al, 2001; Rabin et al, 2006). …”
mentioning
confidence: 99%